Evaluation of the prevalence of Echinococcus multilocularis in dogs that visit off‐leash dog parks in southern Ontario, Canada. (17th December 2020) - Kotwa, Jonathon D.; Greer, Tyler; Jardine, Claire M.; Weese, J. Scott; Isaksson, Mats; Pearl, David L.; Berke, Olaf; Mercer, Nicola; Peregrine, Andrew S.
Abstract: Prior to 2012, Echinococcus multilocularis was not known to occur in any host in Ontario, Canada. However, since that year, five cases of alveolar echinococcosis have been diagnosed in dogs that resided at the western end of Lake Ontario. In addition, E. multilocularis has been shown to be a common infection in wild canids (i.e. coyotes and foxes) across southern Ontario with a high‐risk infection cluster in the area surrounding the western shores of Lake Ontario and northern shores of Lake Erie. In regions endemic for E. multilocularis, dog ownership is considered a risk factor for human alveolar echinococcosis. A study was therefore carried out to determine the prevalence of E. multilocularis intestinal infections in dogs within the high‐risk infection cluster. From May to November 2018, faecal samples were collected from 477 dogs aged ≥6 months that visited 12 off‐leash dog parks in the Halton, Hamilton and Niagara public health units. Faecal samples were analysed via a magnetic capture probe DNA extraction and real‐time PCR method for E. multilocularis DNA. Overall, 0% (97.5% CI: 0%–0.80%) of samples tested positive. This result informs preventive recommendations for E. multilocularis infections in dogs in this region.